Toward the reconstruction of sacred medieval spatialities: Multiscale analysis of the system of eremitical landscapes in southern Portugal from historical records - Volzone, R.; Fontes, J. L. I.; Carapinha, A. da C. P. (Historical Archaeology, 2023)
Reconstruction of the landscape of late medieval southern Portugal is hampered by the scarceness of physical evidence after the subsequent centuries of evolution. The aim of this article is to understand how the spread of eremitical communities in this region interacted with the existing landscape, contributing to its transformation. A multiscale analysis is carried out through the examination of historical records containing scattered data about the landscape system. This methodology is applied to a specific case study, the Portuguese eremitical congregation of São Paulo da Serra de Ossa, in southern Portugal. Although fragmentary and dispersed, primary sources from between 1366 and 1578 are useful in reconstructing the components of this landscape. Initial results show the definition of a typical Mediterranean form of settlement: “agro-sylvo-pastoral”.